ANALISIS POTENSI MAKRO SEKTORAL KOTA JAYAPURA DAN ARAH PENGEMBANGANNYA DIMASA MENDATANG - Yundi Hafizrianda (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2014)
This study generally aims to provide a clear image of the sectoral macro economic potential in Jayapura City. More specific, the objectives are: (a) determine and analyze base sectors in Jayapura City, (b) identify and analyze the performance of economic sectors in Jayapura City in order to know the sectors that have competitive advantage and specialization, (c) establish and analyze the typology of socio-economic potential in Jayapura City and compare it with some other equivalent regency, and (d) establish the direction of the leading commodity based on sectoral development potential. Some analysis tools of macro regional performance indicators are descriptive statistics, LQ, SSA, MRP, Overlay Analysis and Composite Performance Index. Based on the result analysis, it is shown that the economic development Jayapura city has always rested on the potentials that are non-tradable sectors. The non-tradable sectors are hotels, trade, construction, restaurants, transportation, banking, and so on which most of the base is not on the local economy. While tradable sectors that have a very strong local base sectors eg. food crops, fisheries, livestock, micro industrial, become complementary and inferior sectors in Jayapura City economy. Due to the absurd economic development like this, the non-tradable sectors are always dominant over the tradable sectors and never once happened that a fundamental change in the economic structure, causing the distribution of income, employment absorption, and business opportunities, all experiencing high inequality. To improve the conditions of economic performance such as this it is necessary to establish potential development strategy of tradable sectors to lead commodity based that is in an effort to improve the marketing and administration, expanding a partnership in the development of leading commodities, improve the quality of human resources, production, capital and value added commodity, as well as institutional strengthening economic commodity.